THE EFFECTIVENESS OF PROBLEM – BASED LEARNING (PBL) MODEL WITH HOTS ORIENTED TOWARDS THE MATHEMATICS LEARNING OUTCOMES - Rofikoh Khasanah; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
High order thinking skill (HOTS)-oriented PBL learning model emphasizes the use of real problems that can entice students to think high-level in solving problems. This study aims to find more effective learning between mathematics learning using the HOTS-oriented PBL model with mathematics learning using the direct model of mathematics learning outcomes. This study population was all students of class X Muhammadiyah Vocational High School Light Vehicle Engineering 1 Bambanglipuro ( SMK 1 Muhammadiyah Bambanglipuro) academic year 2017/2018, which amounted to 184 students. Samples taken by two classes using the Random Sampling technique, obtained class X Light Vehicle Engineering (TKR) F as control class and class X TKR E as experiment class. The technique of collecting data using the test method. Instrument testing uses validity test and reliability test. The data analysis technique used for the prerequisite test is the normality test with Chi-Square and homogeneity test with the F test formula, while for hypothesis test with t-test. The results showed that at a 5% significant level and dk = 56, it was concluded that (1) there was a difference in mathematics learning results among students whose learning using HOTS-oriented PBL model with students using a direct model. This is indicated by the value = 2,8166 > = 2,0045. (2) Mathematics learning using the HOTS-oriented PBL model is more effective than mathematics learning using a direct model of mathematics learning result. This is shown by = 2,8166 > = 1,6733.